2018
DOI: 10.1016/j.virol.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Detailed mapping of the linear B Cell epitopes of the hemagglutinin (HA) protein of swine influenza virus

Abstract: Using the Hemagglutinin (HA) protein peptide array of H1N1 pdm09 and a panel of swine antisera against various swine influenza H1 and H3 clusters, we identified three immunoreactive epitopes with one (peptide 15) located in HA1 (amino acids 57-71) and two (peptides 121 and 139) in HA2 (amino acids 481-495 and 553-566). Further analysis showed that all swine antisera of H1 clusters efficiently recognized two HA2 epitopes; peptides 121 and 139, with only a subset of antisera reactive to HA1-derived peptide 15. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Interestingly, this position was included in a B-cell epitope proposed by a previous study investigating the A(H1N1)pdm09 subtype. In this study the reaction of the peptide encoding the epitope against a panel of swine sera raised against a panel of H1 and H3 subtypes were tested and showed a reaction, indicating this epitope to be highly immune reactive in pigs [58]. Moreover, the position was also included in a T-cell epitope defined in the human seasonal H1N1 subtype [59].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Interestingly, this position was included in a B-cell epitope proposed by a previous study investigating the A(H1N1)pdm09 subtype. In this study the reaction of the peptide encoding the epitope against a panel of swine sera raised against a panel of H1 and H3 subtypes were tested and showed a reaction, indicating this epitope to be highly immune reactive in pigs [58]. Moreover, the position was also included in a T-cell epitope defined in the human seasonal H1N1 subtype [59].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the lineage of each gene segment was determined by aligning the respective sequences with contemporary swIAV sequences obtained in the Danish swine IAV surveillance program and subsequently neighbor-joining trees were constructed. Furthermore, HA amino acid sequences were annotated for known antigenic sites (Sa, Sb, Ca1, Ca2, and Cb) [5,6,8,55,56], B-cell epitopes [57,58] and T-cell epitopes [59][60][61][62], which were then manually checked for variation. Potential asparagine-linked glycosylation sites of the HA protein was predicted by the program NetNGlyc 1.0 Server [63].…”
Section: Characterization Of the Herd Swiav Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Guo et al also found that the peptide FYHKCDNT was an immunodominant epitope in the 2009 pandemic H1N1 IAV, and the seasonal influenza viruses, induced generation of high volumes of antibodies by organisms [40]. Wang et al proved that peptide CFEFYHKCDNTCMES could be recognized by the antiserum against the H1 subtype swine in uenza virus, and was able to generate antibody responses in pigs via intranasal inoculation [41]. Katherine et al identi ed that peptide YHKCNNECMESVKNGTYD and EFYHKCNNECMES played a role in CD4 T cells response and facilitated the release of IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…The different amino acids present in the HA antigenic sites (Cb, Sa, Sb, Ca1 and Ca2) were calculated by comparing our sequences with reference sequences [ 28 , 54 , 55 , 56 ]. B- and T-cell epitopes were analysed by aligning our sequences with reference sequences [ 57 , 58 , 59 , 60 ] using Clustal-W [ 50 ]. Differences present at seven antigenic sites (1, 2a, 2b, 2c, 2d, 3 and 4) of the NA gene segment were calculated by comparing our sequences with reference sequences [ 61 , 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%